Musik Degung Sunda dalam Konteks Sejarah - Rachmat Herawan (EKSPRESI, 2009)
Degung Sunda Music in The Historical Context. Degung music was originated in Cianjur region and has been developing very well in Bandung. It was originally the music of the menak people who geographically lived in mountain range area. In accordance with the location atmosphere, this music was ethical, calm, in a good arrangement, in a good order, and peaceful. This music has experienced several changes such as the waditra structure change, the status sift from kadaleman music to people music, the repertoire forms change, and the function change from an illustration music to a dance music. Keywords: Degung, waditra, kadaleman, Sundanese music.